Linguistic approaches and modern communication technologies in political discourses in Europe and the USA (contrastive aspect ) - Shkvorchenko, Nataliia; Cherniaieva, Irina; Petlyuchenko, Nataliia (My University, 2021)
In this study, we analyze the political discourse of the United States and Europe in terms of linguistic approaches. Among the methods we use are systemic, structural, functional, content analysis, discourse analysis and thesaurus method. Its application took place within the theory of discourse. The study found that the main difference between the political discourses of Europe and the United States are the forms and means ofcommunication, the formats of their distribution and the massive indicators of inclusion of the population (recipient of political discourse) in the communicative interaction. The difference is also the centralization and the levels at which the discourse develops. For example, the focus of political rhetoric on the institution of the U.S. presidency makes the presidential speech a reflection of public opinion. This is not typical of European countries, as pluralism of opinion is widespread there, communication takes place at local, regional, national, and supranational level. In addition, the European identity is in the process of being deeded. However, both discourses have in common the commitment to the values of democracy, but they manifest themselves differently.
Shkvorchenko Nataliia Linguistic approaches and modern communication technologies in political discourses in Europe and the USA (contrastive aspect) /Nataliia Shkvorchenko, Irina Cherniaieva, Nataliia Petlyuchenko // Сuestiones políticas. – 2021. – Vol. 39, № 70. – P. 815-831.
Keywords: political discourse; political communication; communication technologies; linguistic approaches; comparative politics